Handbook of the Renaissance Europe 1400 - 1600 - McRae, Lee. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1995)
This handbook provides background materials and teaching suggestions for studying the Renaissance at the middle school level. The 16 chapters include: (1) "The Renaissance in Europe: 1400-1600"; (2) "Education"; (3) "Important People"; (4) "Women of the Renaissance"; (5) "How People Lived"; (6) "Health and Medicine"; (7) "What People Wore"; (8) "What People Ate"; (9) "Games and Entertainment"; (10) "Instruments and Music"; (11) "Books, Printing, and Libraries"; (12) "The Age of Exploration"; (13) "Timeline"; (14) "More Important People"; (15) "Reading List"; and (16) "Recordings." Drawings and illustrations related to the time accompany the text. (EH)
Availability: Handbook of the Renaissance, 2130 Carleton Street, Berkeley, CA 94704-3214; telephone: 510-848-5591.
ERIC Note: Part of a National Endowment for the Humanities project entitled "Quest for the Renaissance.".
Practitioners.
Teachers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: European History; Foreign Countries; Instructional Materials; Intermediate Grades; Junior High Schools; Middle Schools; Social Studies; Western Civilization; World History; Europe -- Renaissance; Guides, Non-Classroom.